Is Pulp Inflammation a Prerequisite for Pulp Healing and Regeneration? - Michel Goldberg; Akram Njeh; Emel Uzunoglu (Hindawi Limited, 2015)
The importance of inflammation has been underestimated in pulpal healing, and in the past, it has been considered only as an undesirable effect. Associated with moderate inflammation, necrosis includes pyroptosis, apoptosis, and nemosis. There are now evidences that inflammation is a prerequisite for pulp healing, with series of events ahead of regeneration. Immunocompetent cells are recruited in the apical part. They slide along the root and migrate toward the crown. Due to the high alkalinity of the capping agent, pulp cells display mild inflammation, proliferate, and increase in number and size and initiate mineralization. Pulp fibroblasts become odontoblast-like cells producing type I collagen, alkaline phosphatase, and SPARC/osteonectin. Molecules of the SIBLING family, matrix metalloproteinases, and vascular and nerve mediators are also implicated in the formation of a reparative dentinal bridge, osteo/orthodentin closing the pulp exposure. Beneath a calciotraumatic line, a thin layer identified as reactionary dentin underlines the periphery of the pulp chamber. Inflammatory and/or noninflammatory processes contribute to produce a reparative dentinal bridge closing the pulp exposure, with minute canaliculi and large tunnel defects. Depending on the form and severity of the inflammatory and noninflammatory processes, and according to the capping agent, pulp reactions are induced specifically.